Mirror, Likes, and Loot: The Interplay of Narcissism, FOMO, and Digital Marketing on Compulsive Buying Behavior - Doni Martias; Nofrizal Nofrizal; Rafidianto Wibisono; Nurhayani Lubis; Afvan Aquino; Richa Afriana Munthe (Journal of Consumer Sciences, 2026)
Background: The growth of fashion e-commerce has intensified the use of affiliate marketing, user-generated content, and gamification to improve engagement. These strategies influence consumer psychology, particularly narcissism, increasing susceptibility to Fear of Missing Out (FOMO) and compulsive shopping. Purpose: This study aimed to investigate the effects of digital strategies on narcissism and their role in driving FOMO as well as compulsive fashion purchases in e-commerce. Method: This study conducted a quantitative online survey of 458 e-commerce customers selected via purposive sampling, and analyzed the data using structural equation modeling (SEM) in SmartPLS. Findings: The results showed that affiliate marketing, user-generated content (UGC), and gamification significantly impacted narcissism. Furthermore, narcissism could trigger FOMO and compulsive buying behavior, and FOMO significantly affected compulsive buying. Both narcissism and FOMO played significant roles as positive mediators and moderators in the relationship between exogenous variables and compulsive buying. Conclusions: This study concluded that affiliate marketing, UGC, and gamification significantly increased narcissism, triggering FOMO and compulsive fashion buying in Indonesian e-commerce. The results identified narcissism as a key psychological link between digital marketing strategies and excessive consumption, underscoring the need for ethical marketing practices and stronger consumer self-control. Research implication: This study theoretically showed that affiliate marketing, UGC, and gamification triggered narcissism, leading to FOMO and compulsive buying. Practically, it emphasized the need for the ethical use of these strategies to foster sustainable consumer relationships.